Peran Jabatan Notaris dalam Pembuatan Akta Pengalihan Hak Atas Merek Terdaftar - Kanti Rahayu; Kus Rizkianto; Mukhidin Mukhidin (Kosmik Hukum, 2022)
Marks can be transferred to other parties by registered trademark owners. The transfer can be done from person to person or transfer from one person or several people to a company or corporation. The possibilities that can occur on the transfer of a brand from a personal to a company include selling the brand personally to a certain company. Transfer of Marks has been regulated in Article 41 of the Law on Marks and Geographical Indications concerning the Transfer of Rights and Licenses. Right to Mark can be transferred due to Inheritance; Will; Waqf; Grant; Agreement; or other reasons justified by the provisions of laws and regulations. This study aims to explain the legal arrangements for making a deed of transfer of rights to a registered mark and examine the role of the Notary Position in making a deed of transfer of rights to a registered mark. This study uses library research methods with a normative research approach with qualitative analysis. The result is that the legal arrangements regarding the transfer of rights to registered marks have been regulated in Article 41 of Law no. 20 of 2016 concerning Marks and Geographical Indications which states that rights to registered marks can be transferred by several mechanisms justified by law such as through inheritance, endowments, grants, wills, agreements and other reasons according to the applicable law. Every act of transferring rights to a registered mark must be registered with the Minister accompanied by supporting documents. Once recorded, the transfer of rights to the mark will be announced in the Official Gazette of Marks and may be subject to a fee. Then the terms of the transfer of rights to the registered mark in the form of a deed must be made before a Notary as the official office of the deed maker.Keywords: Notary, Deed, Transfer of Rights, Registered Mark